Individual Teachers' Understanding in Implementing Guidance and Counseling Services for Intellectually Disabled Children - Fitriyani, Fitriyani; Dayanti, Intan Rama; Apriliyanti, Gita Dwi Tamara; Zanah, Laila Syamlatul (Pusdikra-Publishing.com, 2024)
Each teacher's understanding of how to provide guidance and counseling to children with intellectual disabilities is an important aspect to ensure effective education. The aim of this research is to explore teachers' understanding of strategies, challenges and successes in implementing guidance and counseling services for children with intellectual disabilities. The research subject involved the homeroom teacher, class VI C for mentally retarded children. It is hoped that this research will provide insight and become a reference for authors and readers in providing individual guidance and counseling services by understanding mentally retarded children. This research shows that teachers' understanding of the individual needs of children with intellectual disabilities, effective counseling strategies, and parental involvement play an important role in the success of counseling services. However, challenges related to resources, expertise and institutional support were also identified. The meaning of this research is to provide valuable insight into the development of training and support programs for teachers who provide guidance and counseling services for children with intellectual disabilities.